Comparison of Routine and Computer-Guided Glucose Management for Glycemic Control in Critically Ill Patients. - Canbolat, Ozlem; Kapucu, Sevgisun; Kilickaya, Oguz (Critical Care Nurse, 2019)
Background Glycemic control is crucial for reducing morbidity and mortality in critically ill patients. A standardized approach to glycemic control using a computer-guided protocol may help maintain blood glucose level within a target range and prevent human-induced medical errors. Objective To determine the effectiveness of a computer-guided glucose management protocol for glycemic control in intensive care patients. Methods This controlled, open-label implementation study involved 66 intensive care patients: 33 in the intervention group and 33 in the control group. The blood glucose level target range was established as 120 to 180 mg/dL. The control group received the clinic's routine glycemic monitoring approach, and the intervention group received monitoring using newly developed glycemic control software. At the end of the study, nurse perceptions and satisfaction were determined using a questionnaire. Results The rates of hyperglycemia and hypoglycemia were lower and the blood glucose level was more successfully maintained in the target range in the intervention group than in the control group (P <.001). The time to achieve the target range was shorter and less insulin was used in the intervention group than in the control group (P <.05). Nurses reported higher levels of satisfaction with the computerized protocol, which they found to be more effective and reliable than routine clinical practice. Conclusions The computerized protocol was more effective than routine clinical practice in achieving glycemic control. It was also associated with higher nurse satisfaction levels.